Investigação das interações verbais em um análogo experimental de metacontingência - Oda, Lígia Valladares (2009)
This study has the objective to propose an investigation of verbal interaction and its role related to a selection of an experimental analogue of metacontingency, a relevant unit of analysis to understand the cultural evolution. It was intended, then, to answer the following questions: a) What are the relations between verbal interactions and the selection/recurrence of experimentally selected IBCs? b) What are the relations between verbal interactions and the transmission of the experimentally selected IBCs? c) What are the relations between verbal interactions and selection of a metacontingency? To answer those questions, the experiment was started with a participant in front of a work area in a computer, which presented four numbers from O to 9 in 4 windows, and below these, there were other four windows in blank that the participant should also complete with numbers from O to 9; when the participant completed a column (window with the number presented by the computer + window with number chosen by the participant) with a total of an odd number, points were added in a label of "Points", which could, by the end of the session, be exchanged for a value of money. When the total of the column was an even number, points were removed from the participant's label, the value of points and bonuses varied according to the experimental condition. The second experimental condition was characterized by the entry of another participant and the beginning of bonuses consequences, ie, when the total sum of the four blank windows of P1 was to the sum of P2's windows, it was added, then, 300 'Bonus' to each participant (also exchangeable for money). On the third experimental condition, there was a generations change, this way, the oldest participant was replaced by other participant at the end of each round, by all, 11 participants were replaced, and two of them (P10 and P11) were replaced in the fourth condition, when the bonuses consequences were withdrawn. All verbalizations made by the participants were recorded, transcribed and then analyzed in order to be identified according to the trial and participant. The verbalizations were also compared to the numbers given by the computer, the numbers chosen by the participants and the individual and cultural consequences that happened together with verbal interactions. Then, all the first and last verbalizations in each trial were c1assified, the content of the verbalizations was identified (points,and bonuses), all the verbal interactions among the participants were quantified, and finally, all the verbalizations of the first trial in each generation were compared. The examination of verbal interactions analysis showed for this group, that verbal behavior has an important role to select IBCs, such as for its recurrence and transmission across generations, and also exercise a decisive role for selecting a metacontingency, since verbal interactions participate of IBCs selection and enable the production of aggregate outcome and production of cultural consequence